Beyond socioeconomic status: the cross-cultural interplay of perceived teacher social support in reading literacy - Xu, Shuai; Yong, Ping (Frontiers in Psychology, 2025)
Previous research has extensively examined the relationship between student socioeconomic status (SES) and their reading literacy. However, few studies have explored how the different facets of perceived teacher social support (TSS) moderate the SES-reading literacy link, particularly from a cross-cultural perspective. The present study utilized data from the 2022 Programme for International Student Assessment, which encompasses 515,170 students across 70 countries and economies. These countries/economies were grouped into eight distinct cultural clusters based on Cultural Value Orientation Theory: African and Middle Eastern, Confucian, East-Central European, East European, English-speaking, Latin American, South Eastern, and West European cultures. Employing structural equation modeling, we found a consistent positive correlation between SES and reading literacy across all eight cultural contexts. Distinct TSS facets (i.e., teacher support, teacher emotional support, and teacher feedback) exhibited varying moderating effects on the SES-reading literacy relationship across different cultures. Furthermore, the variations in effect size across the eight cultural clusters are explicable by cultural values. Our study underscores the necessity of differentiating the TSS facets and the importance of cultural context in assessing the interactions among the investigated variables.